Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.

Association-dissociation dynamics of ionic electrolytes in low dielectric medium - Ghosh, Deborin; Sakpal, Sushil S.; Chatterjee, Srijan; Deshmukh, Samadhan H.; Kwon, Hyejin; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Ionic electrolytes are known to form various complexes which exist in dynamic equilibrium in a low dielectric medium. However, structural characterization of these complexes has always posed a great challenge to the scientific community. An additional challenge is the estimation of the dynamic association-dissociation time scales (lifetime of the complexes), which are key to the fundamental understanding of ion transport. In this work, we have used a combination of infrared absorption spectroscopy, two-dimensional infrared spectroscopy, molecular dynamics simulations, and density functional theory calculations to characterize the various ion complexes formed by the thiocyanate-based ionic electrolytes as a function of different cations in a low dielectric medium. Our results demonstrate that thiocyanate is an excellent vibrational reporter of the heterogeneous ion complexes undergoing association-dissociation dynamics. We find that the ionic electrolytes exist as contact ion pairs, dimers, and clusters in a low dielectric medium. The relative ratios of the various ion complexes are sensitive to the cations. In addition to the interactions between the thiocyanate anion and the countercation, the solute-solvent interactions drive the dynamic equilibrium. We have estimated the association-dissociation dynamics time scales from two-dimensional infrared spectroscopy. The exchange time scale involving the cluster is faster than that between a dimer and an ion pair. Moreover, we find that the dynamic equilibrium between the cluster and another ion complex is correlated to the solvent fluctuations.

Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.

Does viscosity drive the dynamics in an alcohol-based deep eutectic solvent? - Chatterjee, Srijan; Deshmukh, Samadhan H.; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Deep eutectic solvents, consisting of heterogeneous nano-domains of hydrogen-bonded networks, have evolved into a range of viscous fluids that find applications in several fields. As viscosity is known to influence the dynamics of other neoteric solvents like ionic liquids, understanding the effect of viscosity on deep eutectic solvents is crucial to realize their full potential. Herein, we combine polarization-selective pump-probe spectroscopy, two-dimensional infrared spectroscopy, and molecular dynamics simulations to elucidate the impact of viscosity on the dynamics of an alcohol-based deep eutectic solvent, ethaline. We compare the solvent fluctuation and solute reorientation time scales in ethaline with those in ethylene glycol, an ethaline constituent. Interestingly, we find that the solute's reorientation apparently scales the bulk viscosity of the solvent, but the same is not valid for the overall solvation dynamics. Using the variations in the estimated intercomponent hydrogen bond lifetimes, we show that a dissolved solute does not sense the bulk viscosity of the deep eutectic solvent; instead, it senses domain-specific local viscosity determined by the making and breaking of the hydrogen bond network. Our results indicate that understanding the domain-specific local environment experienced by the dissolved solute is of utmost importance in deep eutectic solvents.

Ligand dynamics time scales identify the surface-ligandinteractions in thiocyanate-capped cadmium sulfide nanocrystals - Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2022)
The nanocrystal surface, which acts as an interface between thesemiconductor lattice and the capping ligands, plays a significant role in theattractive photophysical properties of semiconductor nanocrystals for use in awide range of applications. Replacing the long-chain organic ligands with shortinorganic variants improves the conductivity and carrier mobility of nanocrystal-based devices. However, our current understanding of the interactions betweenthe inorganic ligands and the nanocrystals is obscure due to the lack ofexperiments to directly probe the inorganic ligands. Herein, using two-dimensional infrared spectroscopy, we show that the variations in the inorganicligand dynamics within the heterogeneous nanocrystal ensemble can identifythe diversities in the inorganic ligand-nanocrystal interactions. The liganddynamics time scale in SCN-capped CdS nanocrystals identifies three distinctligand populations and provides molecular insight into the nanocrystal surface.Our results demonstrate that the SCN-ligands engage in a dynamic equilibriumand stabilize the nanocrystals by neutralizing the surface charges through both direct binding and electrostatic interaction.

Does variation in composition affect dynamics when approaching the eutectic composition? - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Chemical Physics, 2023)
Deep eutectic solvent is a mixture of two or more components, mixed in a certain molar ratio, such that the mixture melts at a temperature lower than individual substances. In this work, we have used a combination of ultrafast vibrational spectroscopy and molecular dynamics simulations to investigate the microscopic structure and dynamics of a deep eutectic solvent (1:2 choline chloride: ethylene glycol) at and around the eutectic composition. In particular, we have compared the spectral diffusion and orientational relaxation dynamics of these systems with varying compositions. Our results show that although the time-averaged solvent structures around a dissolved solute are comparable across compositions, both the solvent fluctuations and solute reorientation dynamics show distinct differences. We show that these subtle changes in solute and solvent dynamics with changing compositions arise from the variations in the fluctuations of the different intercomponent hydrogen bonds.

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.

Solvation dynamics and microheterogeneity in deep eutectic solvents - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Physical Chemistry B, 2024)
Deep eutectic solvents have attracted considerable attention due to their unique properties and their potential to replace conventional solvents in diverse applications, such as catalysis, energy storage, and green chemistry. However, despite their broad use, the microscopic mechanisms governing solvation dynamics and the role of hydrogen bonding in deep eutectic solvents remain insufficiently understood. In this article, we present our contributions toward unravelling the micro heterogeneity within deep eutectic solvents by combining vibrational Stark spectroscopy and two-dimensional infrared spectroscopy with molecular dynamics simulations. Our findings demonstrate how the composition, constituents, and addition of water significantly influence the heterogeneous hydrogen bonding network and solvent dynamics within these systems. These insights provide valuable guidance for the design of next-generation solvents tailored to specific applications. By integrating experimental and computational approaches, this work sheds light on the intricate relationship between solvation dynamics and nanostructure in deep eutectic solvents, ultimately paving the way for innovative advances in solvent design.

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity